2004
DOI: 10.1093/gerona/59.10.b997
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of PPAR in Aging, Inflammation, and Calorie Restriction

Abstract: Peroxisome proliferator-activated receptors (PPARs), members of the nuclear hormone receptor superfamily of transcription factors, are key regulators in various pathophysiological processes related to energy metabolism including lipid, carbohydrate metabolism, and inflammation. At present, little information is on the effect of age and calorie restriction (CR) on PPARs. In the present study, we investigated how age and CR (60% of the ad libitum intake) modulate PPARs in kidneys obtained from Fischer 344 rats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 36 publications
6
97
0
2
Order By: Relevance
“…19 -21 Previous studies in the kidney showed that PPAR␥ activity was decreased in aging rats. 12 Our data showed that pioglitazone increased PPAR␥ expression and activity in the aging kidney, which paralleled decreased glomerulosclerosis and interstitial fibrosis. In addition, systemic oxidative stress and intima thickness in renal arteries were decreased in the treatment group (data not shown).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…19 -21 Previous studies in the kidney showed that PPAR␥ activity was decreased in aging rats. 12 Our data showed that pioglitazone increased PPAR␥ expression and activity in the aging kidney, which paralleled decreased glomerulosclerosis and interstitial fibrosis. In addition, systemic oxidative stress and intima thickness in renal arteries were decreased in the treatment group (data not shown).…”
Section: Discussionsupporting
confidence: 51%
“…11 However, there is little information about PPAR modulation during aging. Because expression of PPAR␥ is reduced during aging and TZDs have many beneficial effects on aging-related molecules, 12 we hypothesized that pioglitazone could protect against aging-related renal injury. Our results indeed show that activation of PPAR␥ is protective against aging-related renal injury.…”
mentioning
confidence: 99%
“…In rodents, PPARs seem to play an important role in the delay of aging caused by CR (86,312). In the rat, PPAR nuclear protein, mRNA level, and DNA-binding activity were shown to decrease with age, whereas CR blunted these reductions (391). Alternatively, using microarray technology, PPAR target genes were upregulated early and intensely in the livers of CR mice (22).…”
Section: Calorie Restriction and Agingmentioning
confidence: 99%
“…In particular, the activity of genes involved in PPARγ-dependent adipogenesis is shown to decline with age for AL animals but not for CR animals (Mueller et al 2002). Linford et al (2007) also reported that PPARγ gene expression is reduced with age, but is preserved with CR in WAT, as was similarly found in other tissues (Sung et al 2004;Chung et al 2008). Furthermore, Wang et al (2008) recently demonstrated that decreased adipocyte storage capacity induces lipid accumulation in liver, heart, and skeletal muscle of the db/db-aP2-leptin receptor on an aP2 promoter (Lepr-b) transgenic mice and that ectopic lipid accumulation is related to metabolic syndrome, including T2D.…”
Section: Discussionmentioning
confidence: 71%